The Misuse of Medical Emblems as an Act of Perfidy in the Ibnu Sina Hospital Killing Incident - Muhammad Tsani Prawira (Faculty of Law Universitas Sebelas Maret, 2025)
This study examines the legality of the military operation conducted by the Israel Defence Forces (IDF) targeting the Ibn Sina Hospital, with specific reference to the prohibition against the misuse of medical emblems as enshrined in Articles 37 and 38 of Additional Protocol I (AP I) to the Geneva Conventions. Reports indicate that approximately twelve IDF soldiers disguised themselves as medical personnel to execute a targeted killing operation. This incident potentially contravenes two core provisions of International Humanitarian Law (IHL): Article 37, which prohibits acts of perfidy, and Article 38, which forbids the misuse of protected emblems. The analysis reveals that the operation satisfies the requisite elements constituting an act of perfidy. First, the conduct involved a deliberate breach of legal protections granted under IHL through the feigned status of medical personnel. Second, the act was carried out with the intent to deceive and fatally target specific individuals, thereby unlawfully capitalizing on the protections afforded by IHL. Third, the operation resulted in the confirmed deaths of three Hamas members. Furthermore, the existence of a direct causal nexus between the deceptive appearance and the fatal outcome underscores the interdependence of the two elements. Accordingly, as all four cumulative conditions of perfidy are fulfilled, it can be concluded that the operation amounted to a violation of the prohibition against treacherous conduct as articulated in Article 37 of Additional Protocol I.